THE PIECE OF ART RECOGIDA DE LA MANZANAAS AN EXCUSE FOR THE READING AND INTERPRETATION OF THE TRADITIONAL LANDSCAPE THROUGH AN ICONOGRAPHIC SOURCE: A STUDY FOR STUDENTS OF 2º OF BACCALAUREATE - ROBERTO GARCÍA MORÍS (Didáctica Geográfica)
We reached some conclusions during this study. Firstly, it must be noted that these students between 17 and 18 years old are able to interpret and contextualize the different elements that the author represented in this box about the traditional life of the Asturian peasantry. They’re able to identify both the human elements, and those typical elementsfrom life in the countryside and the illustrated concrete action (harvest of the apple).